An Interpretive Approach in the Sociological Study of Epistemological Issues and Bottlenecks in the Developmental Developments of Iran in the New Era (Theoretic Levels: The Configuration of a Paradigmatic Approach) - Behrouz Aghazadeh; Hossein Abolhasan Tanhaei; alieh shekarbeugi (توسعه اجتماعی, 2021)
The present study’s formation in the epistemological study of Iran's developmental transformations or the same theoretical levels has followed a new paradigmatic approach and has an exploratory base. The research method in this study is qualitative, of the type of action research in the sense of its pragmatic induction. Data collection has been done using library and documentary techniques, and data analysis using qualitative techniques, element analysis, dialectical analysis and finally conceptual and logical analysis. This research’s findings at the theoretical level for epistemological study of developmental transformations deal with why and how the new paradigm approach is configured. The formation of the new paradigm approach, or the Interpretive approach to development, uses the elements of paradigmatic creativity and sociological imagination and is based on the theoretical tools of theoretical epistemology and theoretical editing because it seeks to examine The pragmatic realities of development are a paradigm shift for research. The results indicate that in the framework of the Interpretive approach to development and in the structuring of new developmental transformations; The interpretive dialectical self element is the epistemological manifestation of the modern man or creative actors and the most important sensitive element of the paradigm that emerges in the context of the epistemological system with a number of sensitive epistemological elements. It needs to be able to build new developmental realities by construction social interactions in line with new developments. While observing such social epistemological relations in Iran’s epistemological system, one can understand it’s intertwined challenges.